THE IMPACT OF COVID 19 IN THE DEVELOPMENT OF THE STUDENT BUSINESS GROUP OF THE ACCOUNTING STUDY PROGRAM AT THE AKADEMI AKUNTANSI PGRI JEMBER - Suwarso (STIE Mandala Jember, 2021)
This study aims to determine the impact of covid 19 in the development of the student businessgroup of the accounting study program at the Akademi Akuntansi PGRI Jember 2021. Themethod used in this research is direct observation in the field. From the results of research onseveral student businesses, various findings were obtained. This research is qualitative in naturewith samples taken from students who carry out business activities. The results of this studyindicate that the impact of covid 19 in the development of business groups of students in theaccounting study program at the Akademi Akuntansi PGRI Jember of Accounts has two impacts,namely positive and negative, that this student business group experiences problems withdecreasing product processing, promotion / advertising increases but decreases in sales, pricesand services. experienced an increase with a low profit level, the relationship between businessmembers was maintained well, while the customers continued to establish a morecommunicative relationship, there was an increase in high enthusiasm for striving earnestly andwilling to learnKeywords: Business, Students, Covid 19.